The complete mitochondrial genome of Metapenaeus ensis - Maocang Yan; Lihua Hu; Min Zhang; Dewei Ji; Qianjin Zhou; Jiongming Zhang; Jiong Chen (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome sequence of Metapenaeus ensis was obtained by PCR, containing 37 genes with 13 protein-coding genes, 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs) and a non-coding control region.